Galeri Perencanaan Pembangunan Kota Makassar sebagai Sarana Komunikasi antara Pemerintah dan Masyarakat - Muhammad Surya Riansyah; Andas Budy; Muhammad Zaki (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
The deterioration of social and environmental conditions has given rise to the concept of Sustainable Development on a global scale. This concept has further led to the emergence of the ideas of urban livability and sustainable cities as strategies to address various problems arising in urban areas.However, poorly conceptualized urban planning, limited public knowledge regarding urban development, and the absence of a platform that facilitates communication between citizens and policymakers have become major challenges in realizing sustainable cities. In response to these conditions, the concept of the Makassar Urban Development Planning Gallery was conceived. This facility aims to provide services, information, and coordination for activities related to urban planning and development authorities. It is envisioned to serve as a communication hub, an idea-sharing platform, and a center for information and education between the government and the public. A survey conducted among 187 respondents revealed that the majority agreed on the necessity of a facility functioning as a center for communication and education on urban planning.